Original paper Psychological aspects of atopic dermatitis and contact dermatitis: stress coping strategies and stigmatization - Ograczyk, Alicja; Malec, Justyna; Miniszewska, Joanna; Zalewska-Janowska, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction : Atopic dermatitis (AD) and contact dermatitis (CD) are among the most common out-patient dermatological diseases. Characteristic skin lesions are located mainly on visible body parts and could attract negative interest of the society. As a result, patients feel socially rejected (stigmatized). Stress coping strategies (concrete ways of coping with stress in different situations) can influence this process. Aim : The aim of our study was to compare stress coping strategies and the stigmatization level in AD and occupational hand CD patients. Material and methods : The study group comprised 65 patients of the Centre for Asthma and Allergy Diagnosis and Treatment in Lodz (35 suffering from AD (27 females, 8 males) and 30 – from hand CD with a negative history of atopy (22 females, 8 males)). Methods used: Stigmatization Scale in Dermatological Patients, Coping Orientations to Problems Experienced – COPE, Coping with Skin Disease Scale – SRS-DER . Results : The comparison of stress coping strategies and feelings of stigmatization between AD and CD groups did not demonstrate statistically significant differences (p > 0.05). The AD patients more often used instrumental and emotional stress coping strategies than CD patients (p < 0.05). The AD group with higher disease acceptance presented a lower stigmatization level (p < 0.05). The employment of hopelessness and helplessness strategies in CD patients was associated with stronger stigmatization (p < 0.05). Conclusions : There are differences between stress coping strategies used in AD and CD groups and they influence feelings of stigmatization, thus enhancement of adaptive coping could be conducted in these patients.